1974
DOI: 10.1111/j.1471-4159.1974.tb04312.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Serine Hydroxymethyltransferase and Glycine Transaminase in Several Areas of the Central Nervous System of the Rat

Abstract: —The regional distributions of serine hydroxymethyltransferase (SHMT) and glycine transaminase (GT) have been determined in five areas of the CNS of the rat. The SHMT activity per mg protein varied in these areas in the following order: medulia‐pons and spinal cord > cerebellum > midbrain > telencephalon. The GT activity per mg protein was essentially the same in the four brain areas, whereas, in the spinal cord it was lower. The activity of GT did not correlate with the glycine content (r=−0.45. P > 0.05). Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 32 publications
2
39
0
Order By: Relevance
“…It is of interest to note that the P had a larger percentage of SHMT activity than of MAO activitylin all regions studied. However, when the distribution of LDH (a cytoplasmic enzyme) was determined,it was found to be markedly di~ferent from that noted for SHMT and MAO (Daly and Aprison, 1974a). Thus, these data support the fact that SHMT is mainly, if not exclusively, a particulate enzyme in these areas of the CNS.…”
Section: Enzyme Studiessupporting
confidence: 57%
See 2 more Smart Citations
“…It is of interest to note that the P had a larger percentage of SHMT activity than of MAO activitylin all regions studied. However, when the distribution of LDH (a cytoplasmic enzyme) was determined,it was found to be markedly di~ferent from that noted for SHMT and MAO (Daly and Aprison, 1974a). Thus, these data support the fact that SHMT is mainly, if not exclusively, a particulate enzyme in these areas of the CNS.…”
Section: Enzyme Studiessupporting
confidence: 57%
“…These investigators also found that SHMT is a mitochondrial enzyme. Daly and Aprison (1974a) found that a good correlation exists between SHMT activity/mg-protein and glycine levels when the cerebellar data were not considered (r = 0.997; P<0.05). However, when the SHMT activity per relative number of mitochondria (SHMT/SDH) is calculated (Gregson & Williams, 1969) excellent correlation with glycine levels was found for all five areas studied.…”
Section: Enzyme Studiesmentioning
confidence: 79%
See 1 more Smart Citation
“…In the case of incubation with aminopterin, the preincubation medium already contained 100 µM aminopterin. brain (Daly and Aprison, 1974;Rassin and Gaull, 1975). We have detected both enzymatic activities in astrogliarich primary cultures and therefore propose that glycine is degraded by the cultured cells in the way that one molecule of glycine is cleaved by the GCS, yielding one C1 unit in the form of N 5 ,N 10 -methylenetetrahydrofolate.…”
Section: Discussionmentioning
confidence: 90%
“…At present we cannot resolve these suppositions. Finally, serine has been posited as the immediate precursor to glycine based on brain (Daly and Aprison, 1974) and retinal biochemistry (Dasgupta and Narayanaswami, 1982), and we presumed that, like elevated glutamate levels in GABAergic neurons, we might observe a concordance between enriched serine signals and G+ cells. However, no cell-specific serine enrichment is evident in the goldfish retina.…”
Section: Additional Amino Acid Patternsmentioning
confidence: 99%